Association of Kinesthetic and Read-Write Learner with Deep Approach Learning and Academic Achievement - Rajendra Kumar, Latha; Voralu, K.; Pani, S. P.; Sethuraman, K. R. (Canadian Medical Education Journal, 2011)
Background: The main purpose of the present study was to further investigate study processes, learning styles, and academic achievement in medical students. Methods: A total of 214 (mean age 22.5 years) first and second year students - preclinical years - at the Asian Institute of Medical Science and Technology (AIMST) University School of Medicine, in Malaysia participated. There were 119 women (55.6%) and 95 men (44.4%). Biggs questionnaire for determining learning approaches and the VARK questionnaire for determining learning styles were used. These were compared to the student’s performance in the assessment examinations. Results: The major findings were 1) the majority of students prefer to study alone, 2) most students employ a superficial study approach, and 3) students with high kinesthetic and read-write scores performed better on examinations and approached the subject by deep approach method compared to students with low scores. Furthermore, there was a correlation between superficial approach scores and visual learner’s scores. Discussion: Read-write and kinesthetic learners who adopt a deep approach learning strategy perform better academically than do the auditory, visual learners that employ superficial study strategies. Perhaps visual and auditory learners can be encouraged to adopt kinesthetic and read-write styles to enhance their performance in the exams.